Upadacitinib for psoriatic arthritis refractory to biologics: SELECT-PsA 2. Issue 3 (3rd December 2020) - Mease, Philip J; Lertratanakul, Apinya; Anderson, Jaclyn K; Papp, Kim; Van den Bosch, Filip; Tsuji, Shigeyoshi; Dokoupilova, Eva; Keiserman, Mauro; Wang, Xin; Zhong, Sheng; McCaskill, Reva M; Zueger, Patrick; et al.
Abstract : Background: Upadacitinib is a Janus kinase inhibitor under evaluation for the treatment of psoriatic arthritis (PsA). We evaluated upadacitinib in patients with PsA and prior inadequate response or intolerance to at least one biologic disease-modifying antirheumatic drug (DMARD). Methods: In this 24-week randomised, placebo-controlled, double-blind, phase 3 trial, 642 patients were randomised (2:2:1:1) to once per day upadacitinib 15 mg or 30 mg, placebo followed by upadacitinib 15 mg or placebo followed by upadacitinib 30 mg at week 24. The primary endpoint was the proportion of patients achieving American College of Rheumatology (ACR) 20 response at week 12. Achievement of minimal disease activity (MDA) was assessed at week 24. Treatment-emergent adverse events are reported for all patients who received at least one dose of trial drug. Results: At week 12, significantly more patients receiving upadacitinib 15 mg and 30 mg versus placebo achieved ACR20 (56.9% and 63.8% vs 24.1%; p<0.001 for both comparisons). At week 24, MDA was achieved by more upadacitinib 15 mg-treated (25.1%) and 30 mg-treated patients (28.9%) versus placebo (2.8%; p<0.001 for both comparisons). Generally, the rates of treatment-emergent adverse events were similar with placebo and upadacitinib 15 mg and higher with upadacitinib 30 mg at week 24. Rates of serious infections were 0.5%, 0.5% and 2.8% with placebo, upadacitinib 15 mg and upadacitinib 30 mg, respectively. Conclusion: In this trial of patients with active PsA who had inadequate response or intolerance to at least one biologic DMARD, upadacitinib 15 mg and 30 mg was more effective than placebo over 24 weeks in improving signs and symptoms of PsA. Clinical trial registration number: NCT03104374